END-LESS DECONSTRUCTION OF THE SELF IN SAMUEL BECKETT’S NOVEL THE UNNAMABLE - Matović Тијана (Наслеђе, 2015)
The aim of this paper is to interpret Samuel Beckett’s novel The Unnamable inside the framework of poststructuralist criticism, primarily that of Jacques Derrida. The first part of the paper is dedicated to exploring Beckett’s specific, bilingual situation in relation to how The Unnamable is narratively constructed. The main analysis focuses on the novel’s narrative structure as a process of end-less discursive deconstruction of the narrator’s self, which, nevertheless, continuously aspires toward that end, toward silence. Special emphasis is placed on the analysis of the discursive treatment of the body, narratively positioned as the cultural product and physical setting of such discourse, but also as an insurmountable obstacle in the process of self-deconstruction, which can only go so far. We come to the conclusion that it is via The Unnamable’s stream-of-consciousness narration and its attempted dissolution of the self, established in the Western metaphysical mindset, that Beckett most radically criticized the ideological conception of identity.